(untitled) (Fiep Bulletin - online, 2011)
The aim of this study was to verify whether there is performance transfer on a task performed in a real environment to a virtual gaming environment in individuals with physical disabilities. Participating in the study are 15 participant athletes of adapted table tennis inexperienced in the task of playing table tennis on Nintendo’s Wii Sport Resort. The task was to receive the table tennis ball and return it to the opponent ´s court in the table tennis game of Nintendo’s Wii Sport Resort. The design of the study consisted of performing 100 attempts, with 10 blocks of 10 attempts for each participant. The results indicated that participants presented similar performance in each block and attempts, representing that there was performance transfer in the real environment to the virtual environment. Attributing to this result is the fact that the task of table tennis in the real environment presents greater difficulties, mainly in the increase of extrinsic factors, and thus, performing in a virtual environment is easier. Accordingly, it was concluded that the Nintendo Wii is a technology that falls within the current trend of body appreciation in the processes of interaction, noting the need for more research that compares these tasks in real and virtual environments.